Dengue virus NS1 protein activates immune cells via TLR4 but not TLR2 or TLR6. Issue 5 (21st February 2017) - Modhiran, Naphak; Watterson, Daniel; Blumenthal, Antje; Baxter, Alan G; Young, Paul R; Stacey, Katryn J
Abstract : The secreted hexameric form of the dengue virus (DENV) non‐structural protein 1 (NS1) has recently been shown to elicit inflammatory cytokine release and disrupt endothelial cell monolayer integrity. This suggests that circulating NS1 contributes to the vascular leak that plays a major role in the pathology of dengue haemorrhagic fever and shock. Pathways activated by NS1 are thus of great interest as potential therapeutic targets. Recent works have separately implicated both toll‐like receptor 4 (TLR4) and the TLR2/6 heterodimer in immune cell activation by NS1. Here we have used mouse gene knockout macrophages and antibodies blocking TLR function in human peripheral blood mononuclear cells to show that recombinant NS1, expressed and purified from eukaryotic cells, induces cytokine production via TLR4 but not TLR2/6. Furthermore, the commercial Escherichia coli ‐derived recombinant NS1 preparation used in other work to implicate TLR2/6 in the response is not correctly folded and appears to be contaminated by several microbial TLR ligands. Thus TLR4 remains a therapeutic target for DENV infections, with TLR4 antagonists holding promise for the treatment of dengue disease.